If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -14 = 2x + 13 Reorder the terms: -14 + 5x = 2x + 13 Reorder the terms: -14 + 5x = 13 + 2x Solving -14 + 5x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -14 + 5x + -2x = 13 + 2x + -2x Combine like terms: 5x + -2x = 3x -14 + 3x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 -14 + 3x = 13 + 0 -14 + 3x = 13 Add '14' to each side of the equation. -14 + 14 + 3x = 13 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 13 + 14 3x = 13 + 14 Combine like terms: 13 + 14 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| 6y+12=-66 | | 6xy-3x+2yx= | | X-4/5=9 | | 5(4)-5y=2y+7 | | 5(7)-5y=2y+7 | | 5x+-1=3x+2 | | 2500=5x-325 | | x+-9=-6 | | 2x^4-2x^3=0 | | 2x+7+4x=49 | | 1/4n-3=25 | | 1/6x=3x+5/4+1/3(x-1) | | 6x-(5)+2= | | 12(2.92)+24(2.92)=60 | | 1.2+y=2 | | (x-4)(x+3)+(x-4)(x+8)= | | 90-x=20 | | (2+2x/60)*20=(1.5+5x/60)*20 | | 7x+84=2x+54 | | 2+(2x/60) | | 4x5=5/2^5 | | 8x^3-x=0 | | 2+2x/60 | | 8x^3+x=0 | | -3x-2+6x=10 | | -9+2x-3x=2 | | 5x-5=-6+6x | | 7+6x+x=84 | | -7+5x+4x=83 | | 3x-7=3(5-x) | | x+5+6x=-30 | | -12=-3x+x+6 |